Effects of Embodied Learning and Digital Platform on the Retention of Physics Content: Centripetal Force - Johnson-Glenberg, Mina C.; Megowan-Romanowicz, Colleen; Birchfield, David A.; Savio-Ramos, Caroline (Frontiers in Psychology, 2016)
Embodiment theory proposes that knowledge is grounded in sensorimotor systems, and that learning can be facilitated to the extent that lessons can be mapped to these systems. This study with 109 college-age participants addresses two overarching questions: a) how are immediate and delayed learning gains affected by the degree to which a lesson is embodied, and b) how do the affordances of three different educational platforms affect immediate and delayed learning? Six 50 minute-long lessons on centripetal force were created. The first factor was the degree of embodiment with two levels: 1) low and 2) high. The second factor was platform with three levels: 1) a large scale “mixed reality” immersive environment containing both digital and hands-on components called SMALLab, 2) an interactive whiteboard system, and 3) a mouse-driven desktop computer. Pretests, posttests, and one-week followup (retention or delayed learning gains) tests were administered resulting in a 2 x 3 x 3 design. Two knowledge subtests were analyzed, one that relied on more declarative knowledge and one that relied on more generative knowledge, e.g., hand-drawing vectors. Regardless of condition, participants made significant immediate learning gains from pretest to posttest. There were no significant main effects or interactions due to platform or embodiment on immediate learning. However, from posttest to followup the level of embodiment interacted significantly with time, such that participants in the high embodiment conditions performed better on the subtest devoted to generative knowledge questions. We posit that better retention of certain types of knowledge can be seen over time when more embodiment is present during the encoding phase. This sort of retention may not appear on more traditional factual/declarative tests. Educational technology designers should consider using more sensorimotor feedback and gestural congruency when designing and opportunities for instructor professional development need to be provided as well.